Assessing Exogenous L-Glutamine and PEG Influence on Soybean Adventitious Roots Culture: Lateral Root Morphology and Amino Acid Profiles: L-Glutamine and PEG Influence on Adventitious Roots Culture - Ardhian, Dhike; Mastuti, Retno; Nahampun, Hartinio Natalia (Journal of Tropical Life Science, 2025)
Soybean (Glycine max L. Merr.) plays an important role in global agriculture and provides a primary source of plant nutrition, notably amino acids. However, tropical climates often result in lower amino acid levels than subtropical climates. This study explored the effects of L-glutamine and PEG on enhancing the amino acid content in in vitro soybean adventitious root. In this study, in vitro adventitious roots from the Detap1 soybean variety were treated in a liquid medium with various concentrations of L-glutamine (0, 1, 2, 4, 8, and 16 g.L-1) or PEG (0, 10, 20, 40, 80, and 160 g.L-1) for 8 days. The root biomass was quantified, and the amino acid profile was analyzed using HPLC. L-glutamine or PEG treatments significantly reduced root biomass by inhibiting lateral root initiation. Meanwhile, 20 amino acids were detected in the control and L-glutamine or PEG treatments. The application of a 16 g.L-1 L-glutamine significantly increased amino acid content. PEG treatments also had similar results in root growth inhibition and increased amino acid accumulation. Multivariate analysis showed significant separation between the control and treatment groups, with glutamine playing a crucial role in the group separation. This study demonstrates the potential of in vitro technology to improve amino acid production through adventitious root culture, providing insights into stress responses and metabolic regulations